Hybrid dielectric-plasmonic nanoantenna with multiresonances for subwavelength photon sources - Dmitriev, Pavel A. (2023)
The enhancement of the photoluminescence of quantum dots induced by an optical nanoantenna has been studied considerably, but there is still significant interest in optimizing and miniaturizing such structures, especially when accompanied by an experimental demonstration. Most of the realizations use plasmonic platforms, and some also use all-dielectric nanoantennas, but hybrid dielectric-plasmonic (subwavelength) nanostructures have been very little explored. In this paper, we propose and demonstrate single subwavelength hybrid dielectric-plasmonic optical nanoantennas coupled to localized quantum dot emitters that constitute efficient and bright unidirectional photon sources under optical pumping. To achieve this, we devised a silicon nanoring sitting on a gold mirror with a 10 nm gap in-between, where an assembly of colloidal quantum dots is embedded. Such a structure supports both (radiative) antenna mode and (nonradiative) gap mode resonances, which we exploit for the dual purpose of out-coupling the light emitted by the quantum dots into the far-field with out-of-plane directivity, and for enhancing the excitation of the dots by the optical pump. Moreover, almost independent control of the resonance spectral positions can be achieved by simple tuning of geometrical parameters such as the ring inner and outer diameters, allowing us to conveniently adjust these resonances with respect to the quantum dots emission and absorption wavelengths. Using the proposed architecture, we obtain experimentally average fluorescence enhancement factors up to $654×$ folds mainly due to high radiative efficiencies, and associated with a directional emission of the photoluminescence into a cone of $± 17°$ in the direction normal to the sample plane. We believe the solution presented here to be viable and relevant for the next generation of light-emitting devices.